2019
DOI: 10.1136/bmjopen-2018-023725
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bias assessment of randomised controlled trials referenced in the 2015 American Heart Association guidelines update for cardiopulmonary resuscitation and emergency cardiovascular care: a cross-sectional review

Abstract: ObjectivesTo identify the risk of bias of randomised controlled trials (RCTs) referenced in the 2015 American Heart Association (AHA) guidelines update for cardiopulmonary resuscitation (CPR) and emergency cardiovascular care (ECC).DesignA cross-sectional review.SettingAll RCTs cited as references in the 2015 AHA guidelines update for CPR and ECC were extracted. After excluding non-human trials, studies that analysed existing RCTs, and RCTs published in a letter format, two reviewers assessed the risk of bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
8
0
2
Order By: Relevance
“…Our investigation has shown that drug trials had favourable impact on RoB than non drug trials, which might be related with the strict regulations these pharmaceuticals trials must follow. Similarly, Cho Y et al, found that most of drug trials were at low risk of bias for blinding of participants and personnel, while almost two third of non drug trials were at high risk of bias for blinding of participants and personnel in cardiopulmonary resuscitation and emergency cardiovascular care (24).…”
Section: Discussion Of Findings Considering Other Studiesmentioning
confidence: 98%
“…Our investigation has shown that drug trials had favourable impact on RoB than non drug trials, which might be related with the strict regulations these pharmaceuticals trials must follow. Similarly, Cho Y et al, found that most of drug trials were at low risk of bias for blinding of participants and personnel, while almost two third of non drug trials were at high risk of bias for blinding of participants and personnel in cardiopulmonary resuscitation and emergency cardiovascular care (24).…”
Section: Discussion Of Findings Considering Other Studiesmentioning
confidence: 98%
“…Although these data are limited to the clinical topic areas covered by the Cochrane MOSS network, prior research has reported similar percentages of high or unclear risk of bias across many different clinical areas. [ 23 , 24 ] It is important to note that risk of bias assessments are driven by two factors – the reporting of methods and the actual methods – and interpretation of unclear or high risk may conflate the two. Another possibility for the high number of unclear and high risk of bias assessments could be the misinterpretation of the first version of the Cochrane Risk of Bias tool.…”
Section: Discussionmentioning
confidence: 99%
“…Individual study definitions were used for the outcome analysis (see Additional file 2 : Table S2 for details). The potential risk of bias of the included RCTs was evaluated using the risk assessment tool recommended by the Cochrane Collaboration guidelines (assessing random sequence generation; allocation concealment; blinding of participants and personnel; blinding of outcome assessment; incomplete outcome data; selective reporting; and other risk) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%